Effect of pruning and plant density on yield and quality of bell pepper (Capsicum annuum L.) grown under greenhouse conditions in Costa Rica - Monge-Pérez, José Eladio (2016)
The effect of two types of pruning (Spanish and Dutch) and three planting densities (2,60; 3,25; and 3,90 plants/m2) on the yield and quality of bell pepper cv. Vikingo, was evaluated. Spanish pruning yields more total fruits per plant (14,71) but of less mean weight (163,96 g) than Dutch pruning (10,65 fruits/plant; 180,30 g/fruit). Spanish pruning yields more total fruits/m2 (46,99) and higher total yield (76,35 ton/ha) and commercial yield (67,35 ton/ha) than Dutch pruning (34,11 fruits/m2; 61,17 ton/ha and 52,37 ton/ha, respectively). Plant density doesn’t affect neither the total mean fruit weight nor the total number of fruits/m2, but both total and commercial yield was higher at 3,90 plants/m2 (75,75 and 65,83 ton/ha, respectively) and the number of fruits per plant was higher at 2,60 plants/m2 (14,63 fruits/plant). Spanish pruning showed the highest total yield and the highest total number of fruits/m2, both at 2,60 plants/m2 (75,60 ton/ha; 45,01 fruits/m2) and 3,90 plants/m2 (84,30 ton/ha; 52,90 fruits/m2).